SURVEY FOR THE PRESENCE OF HUMAN HERPESVIRUS 8 (HHV-8) INFECTION IN MOZAMBIQUE - Caterino-de-Araujo, A; Manuel, RCR; Del-Bianco, R; Santos-Fortuna, E; Magri, MC; Silva, JMK; Bastos, R (Revista do Instituto Adolfo Lutz, 2009)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi’s sarcoma (KS), and is endemic in some parts of sub-Saharan. The incidence of KS varies across Africa, and in many countries started after HIV epidemic. Several factors could account for KS incidence, but this incidence is correlated with HHV-8 prevalence. The present study aimed to determine for the first time the HHV-8-seroprevalence in Mozambique (MZ), a country which is experiencing an epidemic of AIDS, and which is surrounded by KS endemic countries. Blood samples were collected on filter paper from 189 individuals of Hospital Central de Maputo, MZ: 57 students of medicine school, 31 individuals from the staff, 67 patients in ambulatorial assistance at Dermatology Department, and 57 hospitalized patients from Dermatology Unit. All participants answered a questionnaire and signed the informed consent before blood collection. Latent and lytic HHV-8 antibodies were searched in eluated sera using “in-house” indirect immunofluorescence assays, at Instituto Adolfo Lutz, São Paulo, Brazil. The study was approved by the ethics committees of institutions, and by the governments of MZ and Brazil. HHV-8-seropositivities of 1.8% and 9.7% respectively, were detected among students and staff, in contrast to 16.4% detected among patients in ambulatorial assistance. Concerning hospitalized patients, 47.1% resulted HHV-8-seropositive; 85.7% in KS patients. Half of KS patients were HIV-1-infected. The low number of individuals in each group analyzed joined to differences in socio-demographic characteristics of individuals do not allowed statistical analysis of results. Great variation in HHV-8 frequencies of infection was detected in Maputo (South of MZ), with low prevalences among healthy individuals. This result suggests that Maputo is not an endemic area of HHV-8. Nevertheless, another study is in progress to confirm these data, now analyzing individuals of different riskfactors and from other regions of MZ.